2013
DOI: 10.1097/bcr.0b013e3182a2aa41
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Risk Factors for Hypertrophic Scar Development

Abstract: Objective Hypertrophic scars (HTS) occur in 30–72% patients following thermal injury. Risk factors include skin color, female gender, young age, burn site, & burn severity. Recent correlations between genetic variations and clinical conditions suggest that single nucleotide polymorphisms (SNPs) may be associated with HTS formation. We hypothesized that a SNP in the p27kip1 gene (rs36228499) previously associated with decreased restenosis after coronary stenting would be associated with lower Vancouver scar sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
56
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 19 publications
1
56
0
Order By: Relevance
“…Several published studies consist of retrospective case note reviews where any documentation of a scar which is red or raised constitutes a diagnosis of HTS [5, 9]. Other studies use the height of the scar alone [10, 11] or VSS [12] to diagnose HTS. In addition, some papers consider hypertrophic scars alone whereas others combine HTS with contracted or keloid scars to give an overview of pathological scarring [13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several published studies consist of retrospective case note reviews where any documentation of a scar which is red or raised constitutes a diagnosis of HTS [5, 9]. Other studies use the height of the scar alone [10, 11] or VSS [12] to diagnose HTS. In addition, some papers consider hypertrophic scars alone whereas others combine HTS with contracted or keloid scars to give an overview of pathological scarring [13].…”
Section: Discussionmentioning
confidence: 99%
“…Gangemi et al showed that female sex, younger age, burn sites on the neck or upper limbs, multiple surgical procedures and meshed skin grafts were all independent risk factors for developing pathological post burn scarring [13]. Hypertrophic burn scars are more common in non-white patient populations [4, 9, 12], and this has also been shown to be true for other types of surgical wounds [15]. Berchialla used these identified risk factors to predict risk of hypertrophic scarring using Bayesian networks [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sweat gland is a kind of important appendage of the skin, which plays some key roles in homeostasis maintenance and body temperature regulation. The skin of patients with an extensive deep burn is repaired by a hypertrophic scar [2] without regeneration of sweat glands, and therefore loses the function of perspiration. Burns survivors feel the heat very much and have to rest at home in summer, which affects their quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…The higher the sum of the scores, the more marked or abnormal the scarring [12]. Thompson et al used a VSS score of > 7 as a way of identifying hypertrophic scars [14]. In this study, we discovered a relationship between the VSS score and the presence of cervical stenosis after ART.…”
Section: Discussionmentioning
confidence: 60%